Nursing management of catheter-related bloodstream infection in a patient with peripherally inserted central catheter placement (1例PICC置管患者导管相关性血流感染的护理) - LIU Yuchao (刘云超); SU Guohua (苏国华); E Haiyan (鄂海燕); HAN Jianping (韩建萍); WANG Yutao (王玉涛); WAN Nannan (王楠楠) (Association of Integrative Nursing, 2021)
This paper reviewed the nursing management of catheter-related bloodstream infection (CRBI) in a patient with peripherally inserted central catheter placement after discharge from hospital. Based on the routine treatment and nursing, the chlorhexidine gluconate dressing and external application of Ruyi Jinhuang powder were used to relieve the upper limb swelling and pain. The combination use of chlorhexidine gluconate dressing and Ruyi Jinhuang powder external application is effective to relieve the symptoms of catheter-related bloodstream infection and improve the rehabilitation of patients. (本文回顾1例经外周静脉置入中心静脉导管(PICC)患者携带管路出院致导管相关性血流感染后拔管的护理措施。在常规治疗基础上, 给予葡萄糖酸氯己定敷料结合如意金黄散外敷, 以缓解患者上肢出现红肿热痛症状。葡萄糖酸氯己定敷料和外敷如意金黄散联合使用治疗导管相关性血流感染效果明显, 能够有效缓解局部症状, 促进康复。)